Study on fluctuant element and attenuation rules of seismo-acoustic wave. (July 2019) - Zhao, Shuang; Zhang, Jian; Guo, Cean; Kou, Dongwei; Zhao, Hongzhi
In order to study the propagation characteristics and attenuation rules of seismo-acoustic wave, in this article, the wave equation and displacement function of the seismo-acoustic wave were established, the propagation process of seismo-acoustic wave was three-dimensional simulated by the finite element software LS-DYNA, and the propagation characteristics and attenuation rules of the seismo-acoustic wave were obtained. The NI data acquisition system was used for data acquisition of the underwater test. The simulation and test results are processed by wavelet transform. Theoretical derivation, simulation calculation, and comparison of test results showed that the seismo-acoustic wave includes first break, spherical compressional wave and shear wave, and cylindrical Scholte wave. At the fluid–solid interface, the compressional wave and shear wave propagation attenuated as 1/ r 2, and Scholte wave propagation attenuated as 1/ r 0.5 . In the depth direction, Scholte wave propagation decays exponentially. Scholte wave is mainly concentrated below 25 Hz. The research results can provide important reference value for the research of using seismo-acoustic wave target recognition.